Systematic review of endovascular intervention and surgery for common femoral artery atherosclerotic disease. Issue 1 (24th December 2018) - Jia, X; Sun, Z D; Patel, J V; Flood, K; Stocken, D D; Scott, D J A
Abstract: Background: Endovascular intervention has emerged as a potential alternative to open surgery in treating common femoral artery (CFA) atherosclerotic disease. The aim of this systematic review was to assess the safety and efficacy of both techniques. Methods: Thirteen electronic databases from 1980 to 3 January 2018 were searched. Study quality was assessed using the National Institute for Health and Care Excellence Interventional Procedure Programme quality assessment tool. Safety and efficacy outcome measures were analysed. Results: Thirty-one studies reporting 813 endovascular procedures and 3835 endarterectomies were included. Only two small RCTs have been reported. The methodological quality of available studies was generally low and follow-up short. Safety endpoint assessment revealed a similar risk of wound haematoma for endovascular intervention and endarterectomy (5·5 (95 per cent c.i. 0·2 to 17·2) versus 3·9 (1·7 to 6·9) per cent respectively), a lower risk of wound infection with endovascular procedures (0 versus 5·9 (3·4 to 9·0) per cent) and a lower risk of wound lymph leakage (0 versus 5·7 (3·3 to 8·6) per cent). Efficacy endpoint assessment at 1 year identified that endovascular intervention had a lower primary patency rate than endarterectomy (78·8 (73·3 to 83·8) versus 96·0 (92·2 to 98·6) per cent respectively), a higher revascularization rate (16·0 (6·1 to 29·4) versus 5·8 (1·0 to 14·2) per cent) and a similar amputation rate (2·7 (1·2 to 4·8) versus 1·9 (0·7 to 3·8) per cent). Conclusion: Endovascular intervention of CFA disease appears to reduce the risk of wound complications but is associated with a lower patency rate and increased rates of subsequent revascularization procedures. Standardization of the endovascular technique and quantification of the proportions of patients suitable for either technique are required. Abstract : Endovascular lower patency